2008
DOI: 10.1002/da.20276
|View full text |Cite
|
Sign up to set email alerts
|

Symptom features of postpartum depression: are they distinct?

Abstract: The clinical features of postpartum depression and depression occurring outside of the postpartum period have rarely been compared. The 16-item Quick Inventory of Depressive Symptomatology-Self-Report (QIDS-SR 16 ) provides a means to assess core depressive symptoms. Item response theory and classical test theory analyses were conducted to examine differences between postpartum (n 5 95) and nonpostpartum (n 5 50) women using the QIDS-SR 16 . The two groups of females were matched on the basis of age. All met D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 38 publications
6
75
1
14
Order By: Relevance
“…An additional new finding is that MDE symptoms vary according to previous episodes of depression. According to previous studies, psychomotor symptoms, decreased energy, changes in appetite, sleep disturbances, poor concentration, and mild suicidal ideation are typical of PPD [6,30,31,36]. In this study, symptoms such as depressed mood, loss of interest/pleasure, psychomotor agitation/retardation, and decreased energy were common with all kinds of histories of depression.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…An additional new finding is that MDE symptoms vary according to previous episodes of depression. According to previous studies, psychomotor symptoms, decreased energy, changes in appetite, sleep disturbances, poor concentration, and mild suicidal ideation are typical of PPD [6,30,31,36]. In this study, symptoms such as depressed mood, loss of interest/pleasure, psychomotor agitation/retardation, and decreased energy were common with all kinds of histories of depression.…”
Section: Discussionsupporting
confidence: 61%
“…All nine SCID symptoms and all SCL-90 symptoms were different between the mothers suffering from major depression and the non-depressed postpartum mothers. The symptom profile was wide, as shown by numerous studies [6,[30][31][32][33][34][35][36][37][38]. Increased or decreased appetite, sleep disturbances, and decreased energy, each of which may be difficult to differentiate from healthy women because of postpartum status, other medical reasons and child care stress were also different [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor sleep quality among women with PPD may compromise performance of critical maternal activities to insure infant safety such as concentration, reaction time, and decision-making (Bernstein et al, 2006). Because infants generally entrain to maternal circadian rhythms, infants of depressed mothers may also experience poor sleep quality, which may further exacerbate maternal depressive symptoms (Hiscock & Wake, 2001).…”
mentioning
confidence: 99%
“…The most important limitation of the EPDS is the fact that although it was specifically designed to screen for PPD, all items are similar to those from general depression scales, meaning that it does not include items about the context of a woman's experience as a new mother. Although perinatal depression symptomatology is not specific, it is influenced by the particular situation of being a mother of a newborn [56] and some authors have reported differences between perinatal depressive episodes and those that occur in other periods, such as, more anxious features, guilty, emotional lability, irritability, and concentration/decision-making difficulties [54,57]; irrational worries about the well-being of the infant; and obsessional thoughts of harming themselves or their infants are not uncommon [58]. Gibson et al [59] systematically reviewed the published evidence on EPDS validity for detecting PPD and AD.…”
Section: Sixthmentioning
confidence: 99%